Effect of Bang® Pre-Workout Master Blaster® combined with four weeks of resistance training on lean body mass, maximal strength, mircoRNA expression, and serum IGF-1 in men: a randomized, double-blind, placebo-controlled trial - Neil A. Schwarz; Sarah K. McKinley-Barnard; Zachary J. Blahnik (Taylor & Francis Group, 2019)
Background The aim of the current study was to determine if 4 weeks of consumption of Bang® Pre-Workout Master Blaster® (BMB; Vital Pharmaceuticals Inc., Weston, FL) combined with resistance training resulted in greater increases in muscle mass and maximal strength compared with resistance training combined with placebo (PLA). Additionally, we aimed to determine if BMB ingestion combined with resistance training preferentially altered resting skeletal muscle expression of microRNAs (miRs) or resting serum insulin-like growth factor (IGF-1). Methods Sixteen recreationally-active men completed the study. The study employed a block-randomized, double-blind, placebo-controlled, parallel design. Participants completed two testing sessions separated by 4 weeks of resistance exercise combined with daily supplementation of BMB or PLA. At each testing session, hemodynamics, body composition, and muscle and blood samples were obtained followed by strength assessments of the lower- and upper-body via measurement of squat and bench press one-repetition maximum (1-RM), respectively. A separate general linear model was utilized for analysis of each variable to determine the effect of each supplement (between-factor) over time (within-factor) using an a priori probability level of ≤0.05. Results No significant effects were observed for dietary intake, hemodynamics, fat mass, body fat percentage, or serum IGF-1. A greater increase in total body mass (3.19 kg, 95% CI, 1.98 kg, 4.40 kg vs. 0.44 kg, 95% CI, − 0.50 kg, 1.39 kg) and lean body mass (3.15 kg, 95% CI, 1.80 kg, 4.49 kg vs. 0.89 kg, 95% CI, − 0.14 kg, 1.93 kg) was observed for the BMB group compared with PLA (p <  0.01). A significant increase over time was observed for miR-23a (p = 0.02) and miR-23b (p = 0.05) expression. A greater increase in squat 1-RM was observed for the BMB group (23.86 kg, 95% CI, 16.75 kg, 30.97 kg) compared with the PLA group (14.20 kg, 95% CI, 7.04 kg, 21.37 kg, p = 0.04). Conclusions BMB supplementation combined with resistance exercise training for 4 weeks resulted in superior adaptations in maximal strength and LBM compared with resistance training with a placebo. No adverse resting hemodynamic or clinical blood safety markers were observed as a result of BMB supplementation. The superior outcomes associated with BMB supplementation could not be explained by resting serum IGF-1 or the skeletal muscle miRs measured, although resting miR-23a and miR-23b expression both increased as a result of resistance training.